Improved depression screening and treatment among low-income pregnant and postpartum women following Medicaid expansion in the U.S - Yoon, Jangho; Harvey, S. Marie; Luck, Jeff (Frontiers in Health Services, 2022)
Objective This study examined the effect of Medicaid expansion in Oregon under the Affordable Care Act on depression screening and treatment among pregnant and postpartum women who gave Medicaid-financed births. Methods Oregon birth certificates were linked to Medicaid enrollment and claims records for 2011–2016. The sample included a policy group of 1,368 women (n = 2,831) who gave births covered by pregnancy-only Medicaid in the pre-expansion period (before 2014) and full-scope Medicaid in the post-expansion period, and the comparison group of 2,229 women (n = 4,580) who gave births covered by full-scope Medicaid in both pre- and post-expansion periods. Outcomes included indicators for depression screening, psychotherapy, pharmacotherapy, and combined psychotherapy-pharmacotherapy, separately for the first, second, and third trimesters, and 2 and 6 months postpartum. This study utilized a difference-in-differences approach that compared pre-post change in an outcome for the policy group to a counterfactual pre-post change from the comparison group. Results Medicaid expansion led to a 3.64%-point increase in the rate of depression screening 6 months postpartum, 3.28%-point increase in the rate of psychotherapy 6 months postpartum, and 2.3 and 1%-point increases in the rates of pharmacotherapy and combined treatment in the first trimester, respectively. The relationships were driven by disproportionate gains among non-Hispanic whites and urban residents. Conclusions Expanding Medicaid eligibility may improve depression screening and treatment among low-income women early in pregnancy and/or beyond the usual two-month postpartum period. However, it does not necessarily reduce racial/ethnic and regional gaps in depression screening and treatment.